(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In 1970, a number of works were carried out to provide the internal affairs bodies with highly qualified and leaders, and the operation of a number of educational institutions at the level of the union affects the increase of experience and qualified personnel in police bodies. a very difficult situation has come. The article talks about the activities of the internal affairs body in maintaining peace in the society.